Efficacy of levetiracetam in the treatment of pediatric epilepsy: A protocol for systematic review and meta-analysis. Issue 8 (25th February 2022) - Pang, Qiming; Li, Bangtao; Zhang, Suli; Li, Jiaoyang; Gu, Shuo
Abstract: Background: To systematically collect, critically evaluate, and synthesize current evidence with respect to the efficacy, safety, and tolerability of levetiracetam as mono- or adjunctive therapy for children and adolescents with all types of epilepsy. Methods: The presentation of methods and results in this systematic review was performed according to the evaluation guidelines for health care interventions provided in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol. Literature retrieval will use the Cochrane Library, Web of Science, PubMed, Embase, Allied and Complementary Medicine Database, China Biomedical Literature Database, China National Knowledge Infrastructure, China Science and Technology Journal Database, Wanfang Database, and Ongoing Clinical Trials Database. The risk of bias of included studies is estimated by taking into consideration the characteristics including random sequence generation, allocation concealment, blinding of patients, blinding of outcome assessment, completeness of outcome data, selective reporting and other bias by Cochrane Collaboration's tool. Data synthesis and analyses are performed using RevMan 5.4 software. Results: The results of this systematic review and meta-analysis will be published in a peer-reviewed journal. Conclusion: Levetiracetam seems to be effective and safe for the treatment of pediatric epilepsy.